(1)H NMR Shows Slow Phospholipid Flip-Flop in Gel and Fluid Bilayers - Marquardt, Drew (Langmuir, 2017)
[Image: see text] We measured the transbilayer diffusion of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) in large unilamellar vesicles, in both the gel (L(β′)) and fluid (L(α)) phases. The choline resonance of headgroup-protiated DPPC exchanged into the outer leaflet of headgroup-deuterated DPPC-d13 vesicles was monitored using (1)H NMR spectroscopy, coupled with the addition of a paramagnetic shift reagent. This allowed us to distinguish between the inner and outer bilayer leaflet of DPPC, to determine the flip-flop rate as a function of temperature. Flip-flop of fluid-phase DPPC exhibited Arrhenius kinetics, from which we determined an activation energy of 122 kJ mol(–1). In gel-phase DPPC vesicles, flip-flop was not observed over the course of 250 h. Our findings are in contrast to previous studies of solid-supported bilayers, where the reported DPPC translocation rates are at least several orders of magnitude faster than those in vesicles at corresponding temperatures. We reconcile these differences by proposing a defect-mediated acceleration of lipid translocation in supported bilayers, where long-lived, submicron-sized holes resulting from incomplete surface coverage are the sites of rapid transbilayer movement.